The relationship of posture working with musculoskeletal disorders (MSDs) in the weaver West Sulawesi Indonesia - Fatmawaty Mallapiang; Azriful; Nildawati; Syarfaini; Masyitha Muis; Adriansyah (Elsevier, 2021)
Objective: This study aims to determine the relationship between work posture and musculoskeletal disorders (MSDs) complaints in Lipa'Sa'be Mandar weavers. Method: This research is a quantitative study with an observational approach using a cross sectional study design on 42 samples selected by purposive sampling (N = 124). Results: All respondents (100%) experienced complaints of MSDs, of the 37 (100%) respondents who weaved with a moderate risk work posture, there were 10 (27.0%) respondents experienced complaints of mild MSDs, 21 (56.7%) complaints of MSDs moderate, and 6 (16.2%) experienced severe MSDs complaints. 5 (100%) respondents who weaved with high-risk work postures, with 1 (20%) mild MSDs complaining and 4 (80.0%) severe MSDs complaints. Results of the chi-Square test with α = 0.05, it shows that there is a significant relationship between work posture and MSDs complaints. Conclusions: Work posture is significantly associated with MSDs complaints in Lipa'Sa'be Mandar weavers.